Influence of A- and B-Site Modifications of (La1-xSrx)yCr0.5-zMn0.5-wNiz+wO3-δ on Electrochemical Impedance Characteristics of Reversible Solid Oxide Cell. Issue 15 (1st January 2019) - Maide, M.; Paiste, P.; Möller, P.; Lust, E.; Nurk, G.
Abstract : Influence of A-site deficiency and chemical composition of B-site (concentration of Ni, Mn, and Cr) on electrochemical performance of hydrogen electrode in (La1-x Srx )y Cr0.5-z Mn0.5-w Niz+w O3-δ |(Sc2 O3 )0.10 (CeO2 )0.01 (ZrO2 )0.89 |La0.8 Sr0.2 FeO3-δ reversible solid oxide fuel cell has been studied. Electrochemical characterization has been carried out in fuel cell and electrolysis regimes. Results indicate that in fuel cell regime most notable limiting steps were detected around 0.5 Hz frequency range and were attributed to gas-solid adsorption-desorption processes. pO2 variation in the oxygen electrode compartment led to small variations in a total impedance of single cells but was not the limiting process. In electrolysis mode, the dissociative adsorption was shown as an important limiting stage and limitations in kinetic region of charge transfer step were remarkable. Increase of A-site deficiency caused a significant increase in high-frequency series resistance as well as some increase of total polarization resistance. Variation in B-site composition had a significant influence on electrochemical performance with very different frequency dependence of impedance. Highest current density values of 0.27 and 0.66 A cm −2 at unit cell potentials of 0.9 and 1.5 V, respectively, at 850°C were measured for La0.75 Sr0.25 Cr0.3 Mn0.5 Ni0.2 O3-δ  (fuel cell mode) and (La0.8 Sr0.2 )x Cr0.49 Mn0.49 Ni0.02 O3-δ (electrolysis mode) in hydrogen fuel gas with pH2 O = 0.03 and 0.30 atm, respectively.